Stratospheric intrusion may aggravate widespread ozone pollution through both vertical and horizontal advections in eastern China during summer - Chang, Fengyi; Li, Jiandong; Li, Nan; Liao, Hong (Frontiers in Environmental Science, 2023)
Stratospheric intrusion (SI) is an important source of tropospheric ozone (O3). Here, we used the online coupled Weather Research and Forecasting-Chemistry (WRF-Chem) model to simulate a typical SI event that occurred over eastern China on 15–19, July 2016 and investigate the impacts of SI on near-surface O3 pollution. The results show that the large-scale circulation of SI was characterized by a deep trough over central China and South Asia high and Western Pacific Subtropical high located to the east and west of the deep trough, respectively. With the evolution of the deep trough, the strong downdrafts behind the trough lead to O3-rich air injected into the lower troposphere across eastern China. By using a tracer tagging method in WRF-Chem, we quantified the SI contributed up to 6.5 ppb to the surface O3 concentration. According to the integrated process rate analyses, which were employed to quantify the contribution of different physical/chemical processes to O3, the advection process dominated variations in troposphere O3 with positive contribution ranging from 0.1 to 13.8 ppb h-1. As altitude decreases, the contribution of advection diminishes as the intensity of the SI gradually weakens. Although the vertical advection contributed limited O3 that directly reached the ground, we revealed that the SI has significant impact on near-surface O3 over a large territory of eastern China through regional transport by horizontal advection process. Below 691 m, the positive contribution of horizontal advection to O3 ranges from 1.6 to 13.4 ppb h-1. This study highlights the natural effect of SI on summertime O3 pollution in eastern China and will help the development of a future O3 pollution alert system.